2022
DOI: 10.1136/ebmental-2021-300409
|View full text |Cite
|
Sign up to set email alerts
|

Self-harm, somatic disorders and mortality in the 3 years following a hospitalisation in psychiatry in adolescents and young adults

Abstract: BackgroundThere is limited recent information regarding the risk of self-harm, somatic disorders and premature mortality following discharge from psychiatric hospital in young people.ObjectiveTo measure these risks in young people discharged from a psychiatric hospital as compared with both non-affected controls and non-hospitalised affected controls.MethodsData were extracted from the French national health records. Cases were compared with two control groups. Cases: all individuals aged 12–24 years, hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 30 publications
5
11
0
Order By: Relevance
“…Our data were consistent with past studies that showed excess mortality among patients discharged from inpatient psychiatric care compared with the general population 6–11,14,24 . One novel finding of the study is that although unnatural‐cause mortality (especially suicide) showed a more marked relative risk elevation than natural‐cause mortality, natural‐cause mortality was the key driver of the mortality gap between patients and matched individuals as early as the first 3 months post‐discharge.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data were consistent with past studies that showed excess mortality among patients discharged from inpatient psychiatric care compared with the general population 6–11,14,24 . One novel finding of the study is that although unnatural‐cause mortality (especially suicide) showed a more marked relative risk elevation than natural‐cause mortality, natural‐cause mortality was the key driver of the mortality gap between patients and matched individuals as early as the first 3 months post‐discharge.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with severe mental disorders have an increased all‐cause mortality risk, 1–3 with an estimated reduction in life expectancy of 10 years 4 . This mortality gap seems to have grown in recent decades 4–6 and is more pronounced among the most severely ill who have been psychiatrically hospitalized 6–8 . Past research has found excess mortality among hospitalized psychiatric patients compared with non‐hospitalized patients or the general population 6,7,9–13 .…”
mentioning
confidence: 99%
“…These national data are used for the allocation of hospital budgets, which encourages improvements in data quality in terms of coherence, accuracy and exhaustiveness. These hospital data have been used in medical research for many years ( Goueslard et al 2018 ; Fabrice Jollant, Goueslard, et al 2022 ), and their quality has been confirmed in recent studies on SARS-CoV-2 ( Beltramo et al 2021 ; Mariet et al 2021 ).…”
Section: Methodsmentioning
confidence: 86%
“…We also cannot discount that a number of patients infected with SARS-CoV-2 were not hospitalized. Furthermore, it is possible that a large number of patients who self-harmed were not hospitalized, with some recent work suggesting that 40% of self-harm does not result in hospitalization in France ( Fabrice Jollant, Hawton, et al 2022 ).. Additionally, other confounding factors such as the level of social stringency (social restrictions), infection (number of new cases and deaths and associated fear), and economic difficulties (either prior to or during the pandemic) could not be incorporated into our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that these national data are used for the allocation of hospital budgets encourages improvement in data quality in terms of coherence, accuracy, and exhaustiveness. Therefore, these hospital data have been used in medical research for many years [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], and their quality has been confirmed in recent studies on COVID-19 [ 5 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%